Femoral shaft fracture in 265 children: Log-normal correlation with age of speed of healing - Skak, SØRen Valdemar; Jensen, Tim Toftgård (Acta Orthopaedica, 1988)
After exclusion of delayed unions and pseudoarthroses in teenagers, the time required for union of 275 consecutive fractures of the femoral diaphysis in children followed a log-normal pattern with a constant 10 percent coefficient of variation and a geometric mean increasing uniformly by 0.7 weeks per year. Multiple injuries increased, and operative treatment reduced the geometric mean time for fracture healing.